PENGARUH PRICE TO BOOK VALUE DAN PRICE EARNINGS RATIO TERHADAP RETURN SAHAM (Studi Pada Saham Perusahaan Sektor Manufaktur Yang Listed di Bursa Efek Indonesia Periode Tahun 2009 â 2011) - 11.42.02.0055, Landep Jadmiko (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study examined the effect of Price Earnings Ratio and Price to Book Value of Stock Returns (study at Manufacturing Companies Listing in Indonesian Stock Exchange since 2009 until 2011 period). The sample in this study is a manufacturing company listed in Indonesian Stock Exchange (IDX) in span of years 2009â2011. Study sample is as much as 133 companies with 306 observations. Analysis of data using multiple regression analysis to all hyphotesis.The results showed that Price Earnings Ratio have a significant positive effect to Stock Returns. Price to Book Value have a significant negative effect to Stock Returns. With Goodness of Fit Test showed that Price Earnings Ratio and Price to Book Value given effect to Stock Returns. Keyword: Price Earnings Ratio, Price to Book Value and Stock Returns